Extension of operational regime in high-temperature plasmas and effect of ECRH on ion thermal transport in the LHD. (4th July 2017) - Takahashi, H.; Nagaoka, K.; Murakami, S.; Osakabe, M.; Nakano, H.; Ida, K.; Tsujimura, T.I.; Kubo, S.; Kobayashi, T.; Tanaka, K.; Seki, R.; Takeiri, Y.; et al.
Abstract: A simultaneous high ion temperature ( T i ) and high electron temperature ( T e ) regime was successfully extended due to an optimized heating scenario in the LHD. Such high-temperature plasmas were realized by the simultaneous formation of an electron internal transport barrier (ITB) and an ion ITB by the combination of high power NBI and ECRH. Although the ion thermal confinement was degraded in the plasma core with an increase of T e / T i by the on-axis ECRH, it was found that the ion thermal confinement was improved at the plasma edge. The normalized ion thermal diffusivity χ i / T i 1.5 at the plasma edge was reduced by 70%. The improvement of the ion thermal confinement at the edge led to an increase in T i in the entire plasma region, even though the core transport was degraded.